2018
DOI: 10.1109/jbhi.2017.2782209
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an mHealth-Based Adjunct to Outpatient Cardiac Rehabilitation

Abstract: A pilot study was conducted to determine if a smartphone-based adjunct to standard care could increase the completion rate of a cardiac rehabilitation program (CRP). Based on historical completion rates, 66 participants who were about to commence a hospital-based CRP were randomized so that half received three devices embedded with near-field communication, namely, a smartphone [pre-installed with an application (app) designed specifically for cardiac rehabilitation], portable blood pressure monitor, and weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 47 publications
2
44
0
1
Order By: Relevance
“…Del Rosario et al [ 33 ] randomized patients undergoing home-based or hospital-based CR for the first time to receive a sphygmomanometer and weighing scale that could transmit data via a mobile phone using near field communication technology as an adjunct to standard CR or standard CR alone. The authors noted an improvement in CR completion rates within the intervention arm (27/33, 88% vs 20/33, 67%; P =.04).…”
Section: Resultsmentioning
confidence: 99%
“…Del Rosario et al [ 33 ] randomized patients undergoing home-based or hospital-based CR for the first time to receive a sphygmomanometer and weighing scale that could transmit data via a mobile phone using near field communication technology as an adjunct to standard CR or standard CR alone. The authors noted an improvement in CR completion rates within the intervention arm (27/33, 88% vs 20/33, 67%; P =.04).…”
Section: Resultsmentioning
confidence: 99%
“…A total of four studies were evaluated in meta-analysis. The selected studies were from three different types: four randomized controlled trials/studies [2527, 29], three non-controlled before-after studies [22–24] and one controlled before-after study [28]. When all studies were considered together, a total of 506 participants were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…2, the quality of four RCTs [2527, 29] were summarized by using the Cochrane’s risk of bias table of Review Manager 5.2. Further, a total of four studies [2527, 29] correctly reported the generation of random sequences and only one study [27] explicitly mentioned that the allocation was concealed. Participants were blinded in three of the selected studies [26, 27, 29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations